PERSPEKTIF BEBERAPA ALIRAN ISLAM TENTANG DASAR KEYAKINAN DALAM ISLAM - Fikri, Shofil; Izul Haq, Agung; Aiman, Ummu (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2024)
Concept of faith Kalam experts say that globally faith consists of Al-Tasdiq bi Al-Qalb, Al-Iqrar bi Al-Lisan, and Al-'Amal bi Al-Jawarih. In another editorial it is mentioned as Al-'Amal bi Al-Arkan which means carrying out all the pillars of Islam. In the concept of faith, the differences and similarities of the scholars revolve around this element. In discussing the actions of humans and God. Some say that humans are independent creatures who control themselves. So, what humans do is purely from their actions. There are also those who say that all human actions are from God, and humans do not have any ability to control themselves. Likewise regarding Allah's word, there are those who say that Kalamullah is Qadim, and there are also those who say that Kalamullah is Hadith (new) according to people who say that Kalamullah is a creature. This research was taken from several data and references in the form of relevant articles and analyzed the data by drawing conclusions. In this article we will discuss the comparative flow of Iman and Kufr, Revelation and Reason, the actions of humans and God and their characteristics.